Réponses

2013-09-12T20:03:11+02:00
F = -1*5/6*5 + 1*3/(-10)*3 = -5/30 + 3/(-30) = -5/30 + -3/30 = -8/30 = -4/15
H = 3/(-4) : -9/40 = 3/(-4) * 40/(-9) = 120/36 = 10/3
I = (16*3*5)/(9*14*8) = 240/1008 = 5/21
J = 15 : 25/3 = 15/1 : 25/3 = 15/1 * 3/25 = 45/25 = 9/5
K = (3/4)² = 3²/4² = 9/16
L = 3^(2/4) = 3^(1/2) = racine carrée de 3
Peux tu réécrire le M, j'ai du mal à voir ce qui va ensemble (peut-être un manque de parenthèses...)
Pour le M : (3/4 - 5/2) / 7= (3/4 - 10/4) / 7 = (-7/4) / 7 = (-7/4) / (7/1) = (-7/4) x (1/7) = -1/4